Escaping Deleterious Immune Response in Their Hosts: Lessons from Trypanosomatids - Geiger, Anne; Bossard, Géraldine; Sereno, Denis; Pissarra, Joana; Lemesre, Jean-Loup; Vincendeau, Philippe; Holzmuller, Philippe (Frontiers in Immunology, 2016)
The Trypanosomatidae family includes the genera Trypanosoma and Leishmania, protozoan parasites displaying complex digenetic life cycles requiring a vertebrate host and an insect vector. Trypanosoma brucei gambiense, T. cruzi and Leishmania spp are important human pathogens causing Human African Trypanosomiasis (HAT or Sleeping Sickness), Chagas’ disease, and various clinical forms of Leishmaniasis, respectively. They are transmitted to humans by tsetse flies, triatomine bugs or sandflies and affect millions of people worldwide. In humans, extracellular African trypanosomes (T. brucei) evade the hosts’ immune defences, allowing their transmission to the next host, via the tsetse vector. By contrast, T. cruzi and Leishmania sp. have developed a complex intracellular lifestyle, also preventing several mechanisms to circumvent the host’s immune response. This review seeks to set out the immune evasion strategies developed by the different trypanosomatids resulting from parasite-host interactions and, will focus on: clinical and epidemiological importance of diseases; life cycles: parasites-hosts-vectors; innate immunity: key steps for trypanosomatids in invading hosts; deregulation of antigen presenting cells; disruption of efficient specific immunity; and the immune responses used for parasite proliferation.